Ultracentrifuge methods for the analysis of polysaccharides, glycoconjugates, and lignins - Harding, Stephen E.; Adams, Gary G.; Almutairi, Fahad; Alzahrani, Qushmua; Erten, Tayyibe; Samil Kök, M.; Gillis, Richard B. (Academic Press, 2015)
Although like proteins, polysaccharides are synthesized by enzymes, unlike proteins there is no template. This means that they are polydisperse, do not generally have compact folded structures, and are often very large with greater nonideality behavior in solution. This chapter considers the relevant analytical ultracentrifuge methodology available for characterizing these and related carbohydrate-based systems and information this methodology supplies, in terms of sizes, shapes, and interactions using a comprehensive range of examples, including glycoconjugates and lignins. The relevance and potential of recent software developments such as SEDFIT-MSTAR, the Extended Fujita algorithm, and HYDFIT are considered.